Tingkat Fertilisasi Oosit Sapi Silangan Simmental Peranakan Ongole dan Limousin Peranakan Ongole Secara In Vitro - Hermilinda Parera (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Crossbreeding program by artificial insemination in Indonesian have use from Simmental and Limousin to local cows of Ongole Grade. Offspring from this crossbred called SimPO and LimPO which has advantages such as a large birth weight and rapid growth. The disadvantages of SimPO and LimPO cows are decreased of reproduction performance of Fenotipe 2 (F2) such as pregnancy rate being lower. Pregnancy stage will occur when oocyte had fertilized and had reached to embryos cleavage stage.The aims of this research was to determined in vitro fertilization rate of SimPO and LimPO oocyte. Ovaries from local abbotoir grouped into PO (control), SimPO and LimPO. Cumulusoocyte complexes quality A and B were used for this research. Oocytes were fertilized using frozen semen of Simmental with concentration 5 x 106 cells / ml in Brackett oliphant (BO) medium. In vitro fertilization rate to observed polymorphonuclear (PMN) formation 10 hours after insemination using 1% aceto orcein staining to fertilized oocytes. Fertilized oocytes were washed were transferred into culture and incubated at 38,5 ° C, with 5% CO2 and 95% humidity. These results indicate that in vitro fertilization rate of oocytes did not any significant differences between groups